Mechanisms of domination and representations of resistance in contemporary Libyan narrative: A cultural approach to Najwa Bin Shatwan’s novel, (Slave Pens). - Huwair Sweilem, Raad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This research seeks to uncover the mechanisms of cultural hegemony and the manifestations of resistance in contemporary Libyan narrative through a cultural approach to the novel *Slave Pens* by Libyan novelist Najwa Binshatwan. The novel serves as a narrative model that reveals implicit power structures and their mechanisms of operation within the cultural framework. The research begins with the premise that narrative discourse not only represents reality but also contributes to its production and reshaping through symbolic systems that, on the one hand, reinforce hegemony, and on the other hand, generate forms of resistance. The research employs the cultural method as a theoretical and procedural framework for uncovering these implicit cultural systems. It draws upon the concepts of cultural hegemony in Antonio Gramsci’s work, power and discourse in Michel Foucault’s work, and symbolic violence in Pierre Bourdieu’s work to analyze how the novel produces patterns of hegemony, particularly ethnic, social, and symbolic hegemony, through narrative representations that contribute to reproducing cultural hierarchies and entrenching subjugated consciousness. The research also reveals manifestations of resistance that appear in multiple forms, including deconstructing the dominant discourse, reclaiming the marginalized self, and reshaping identity as a countercultural practice that seeks to undermine symbolic authority. DOI: https://doi.org/10.54633/2333-025-058-015